Sodium Iodide Symporter and Phosphatase and Tensin Homolog Deleted on Chromosome Ten Expression in Cholangiocarcinoma Analysis with Clinicopathological Parameters (Gut and Liver, 2012)
Background/AimsThis study was performed to investigate the correlation of sodium iodide symporter (NIS) expression with the functionality and loss of phosphatase and tensin homolog deleted on chromosome ten (PTEN) expression in human cholangiocarcinoma (CCA).Methods : Immunohistochemistry for the expression of NIS and PTEN was performed in 60 biopsy specimens of CCA. The clinicopathological parameters were retrospectively identified from medical records. The expression pattern of NIS and loss of PTEN expression were analyzed in association with the clinicopathological characteristics, including survival.Results : Normal biliary trees displayed NIS expression, but hepatocytes did not. NIS expression was divided into two patterns: cytoplasmic and membranous. Fifty-nine cases, all except for one case, displayed NIS expression in tumor cells. Twenty-two cases (33.3%) were mixed pattern, and 39 cases (65.05%) were cytoplasmic pattern; the pure membranous pattern was not noted. There was no association between the NIS expression pattern and clinicopathological parameters, including age, sex, differentiation grade, T stage and tumor, node, metastasis stage (p>0.05). The survival rates were similar among various NIS expression patterns. Normal hepatocytes and biliary trees exhibited PTEN expression in the nucleus and cytoplasm. CCA cells displayed nuclear staining. Thirty-six (60.0%) of 60 cases displayed a loss of PTEN expression. The loss of PTEN expression was observed in the advanced T-stage group (p=0.0036), but there was no association between the loss of PTEN expression and other clinicopathological parameters (p>0.05). No association between the loss of PTEN expression and survival was noted.Conclusion : sNIS is expressed in most types of human CCA. The expression pattern suggests a role in cancer development. PTEN loss expression is common in the context of human CCA, especially in the advanced T stage.